Synthesis of New Lipophilic Phosphonate and Phosphonamidate Analogues of N-Acetylmuramyl-L-alanyl-D-isoglutamine Related to LK 423 - Gobec, Stanislav (Molecules, 2002)
A syntheses of three new muramyl dipeptide (MDP) analogues related to LK 423 as potential immunomodulators are presented. The dipeptide part of the lead compound was modified by introducing a phosphonamide isostere instead of the amide bond between L-alanine and D-glutamic acid (or D-isoglutamine), yielding new MDP analogues 5 and 9. Furthermore, the amide bond between L-Ala and D-Glu was replaced by a phosphonate isostere, giving peptidyl phosphonate 14. The scope and limitations of the synthetic strategies employed are discussed.